The Ten Commandments : The Significance of God's Laws in Everyday Life - Schlessinger, Laura Dr. and Vogel, Stewart (New York A Cliff Street Book, 1999)
A radio talk-show host and a rabbi bring the ten commandments into the twentieth century with an honest look at their relevance and significance in today's world
Keywords: Ten commandments -- Conduct of life -- Christian ethics